Dinámicas lingüísticas de las situaciones de contacto - Palacios, Azucena; Sanchez Paraíso, María (De Gruyter, 2021)
The volume offers in-depth analyses of contact situations between Spanish and other languages, showing how language variation and change are part of the complex linguistic dynamics that characterize contact areas. Aimed at contact linguistics experts, it gathers theoretical frameworks as well as case studies about these processes, both in diachronic and synchronic perspectives.